Stress responses of the sea cucumber Holothuria forskali during aquaculture handling and transportation. Issue 9 (20th October 2016) - Tonn, Nina; Novais, Sara C.; Silva, Cátia S. E.; Morais, Hugo A.; Correia, João P. S.; Lemos, Marco F. L.
ABSTRACT: Animal welfare during handling and transportation to aquaculture facilities or public aquaria is commonly estimated by addressing injury and mortality levels. Although these procedures have been optimized for different species, data on individual species' cellular capabilities to tolerate stress are still scarce. In the present study, several biomarkers related with oxidative stress and energy metabolism were assessed in Holothuria forskali during animal acclimation, pre-transport, transport and quarantine. Combined analyses confirmed that sea cucumbers experienced high oxidative stress during transport, but had the capability to deal with it using a complex of cellular defence mechanisms, which enabled recovery from oxidative stress without permanent damage. Through a better understanding of individual species and the development of optimal parameters, this approach has the potential to improve animal wellbeing during and after acclimation, transportation and recovery processes.